Variation factors of paraoxonase in blood and in HDL lipoproteins in dairy cow - Trevisi, E.; Grossi, P.; Bacchetti, et al., T. (Progress in Nutrition, 2012)
Paraoxonase-1 (PON) is an antioxidant enzyme synthesized by liver and mainly associated with high density lipoproteins (HDL). Aim of this study was to investigate the alterations of PON1 activity in plasma (pPON) or bound to HDL (HDL-PON) in relation to inflammatory conditions and physiological stages. Between -30 to +300 days from calving, 9 cows were monitored for metabolic and inflammatory profiles, milk yield, body condition score and feed intake. Cows were divided in 2 groups based on their response to postpartum inflammatory stimulus (high and low Liver Functionality Index: HI-LFI and LO-LFI). pPON decreased after calving (P